Does Treatment Order Matter? Investigating the Ability of Bacteriophage to Augment Antibiotic Activity against Staphylococcus aureus Biofilms - Kumaran, Dilini; Taha, Mariam; Yi, QiLong; Ramirez-Arcos, Sandra; Diallo, Jean-Simon; Carli, Alberto; Abdelbary, Hesham (Frontiers in Microbiology, 2018)
The inability to effectively treat biofilm-related infections is a major clinical challenge. This has been attributed to the heightened antibiotic tolerance conferred to bacterial cells embedded within biofilms. Lytic bacteriophages (phages) have evolved to effectively infect and eradicate biofilm associated cells. The current study was designed to investigate the ability of phage treatment to enhance the activity of antibiotics against biofilm-forming Staphylococcus aureus. The biofilm positive S. aureus strain ATCC 35556, the lytic S. aureus phage SATA-8505, and five antibiotics (cefazolin, vancomycin, dicloxacilin, tetracycline and linezolid) routinely used to treat S. aureus infections, were examined in this study. The ability of the SATA-8505 phage to augment the effect of these antibiotics against biofilm cells was assessed by exposing them to one of the following five treatments: i) antibiotics alone, ii) phage alone, iii) a combination of the two treatments simultaneously, iv) staggered exposure to the phage followed by antibiotics, and v) staggered exposure to antibiotics followed by exposure to phage. Following treatment, the biofilm cells were dislodged and enumerated. The results demonstrate that treatment with either SATA-8505, antibiotics, or the simultaneous exposure of the biofilms to the two agents resulted in minimal reduction of viable biofilm associated cells. However, a significant reduction (up to 3 Log CFU/mL) was observed when the phage treatment preceded antibiotics. This effect was most pronounced with vancomycin and cefazolin which exhibited synergistic interactions with SATA-8505, particularly at lower antibiotic concentrations. This in vitro study serves as a proof of principle for the ability of bacteriophages to augment the anti-biofilm activity of antibiotics, and demonstrates that therapeutic outcomes can be influenced by the sequence of application of these therapeutic agents, and the nature of their interactions. Further investigation into the interactions between various lytic bacteriophages and antibiotics could provide a foundation to devise antibiotic- phage pairings that could serve to direct anti-biofilm therapeutic strategies.